2015
DOI: 10.11336/jjcrs.6.50
|View full text |Cite
|
Sign up to set email alerts
|

Effect of swallowing rounds on the outcome of dysphagic patients

Abstract: Objective: To retrospectively investigate the effect of ward rounds to check swallowing function (hereafter, swallowing rounds) on the outcome of dysphagic patients. Methods: Upon requests from ward nurses or clinical departments in our hospital, a full-time certified nurse specialist in dysphagia examines the general condition of patients and performs screening for dysphagia. For patients who require detailed investigations, a transdisciplinary dysphagia care team conducts ward rounds and evaluates these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 14 publications
0
10
5
Order By: Relevance
“…Thin liquids are more easily aspirated than thick liquid [16][17][18]; therefore, when performing VE at our institution, we generally administer a thick liquid bolus first, and in case of aspiration, a thin liquid bolus is not typically administered. In our previous study wherein VE was performed on 998 hospitalized patients, 7% of the patients had a DSS score of 1, and 31% had a score of 2 [12]; thus, the cases in the present study were clearly less severe. Thin liquids are not administered in more severe cases of dysphagia; therefore, we believe that further research is necessary to determine the Hyodo scores assessed using thick liquids or jelly.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Thin liquids are more easily aspirated than thick liquid [16][17][18]; therefore, when performing VE at our institution, we generally administer a thick liquid bolus first, and in case of aspiration, a thin liquid bolus is not typically administered. In our previous study wherein VE was performed on 998 hospitalized patients, 7% of the patients had a DSS score of 1, and 31% had a score of 2 [12]; thus, the cases in the present study were clearly less severe. Thin liquids are not administered in more severe cases of dysphagia; therefore, we believe that further research is necessary to determine the Hyodo scores assessed using thick liquids or jelly.…”
Section: Discussionmentioning
confidence: 44%
“…At this institution, patients with suspected dysphagia are screened by a certified dysphagia nurse or a physiatrist. If a more detailed examination is required, written informed consent is obtained from the patient or a proxy, and swallowing rounds are performed with VE [12]. VE has been performed for a long time at our institution using 4-mL boluses of liquid, so we used 4-mL boluses to determine the Hyodo scores.…”
Section: Methodsmentioning
confidence: 99%
“…For patients who were dead at discharge, the main feeding method before death was used as the feeding method at discharge. Furthermore, the results obtained from this study were compared with those reported by Toda et al [9]. The statistical software SPSS Statistics 19 (IBM, Japan) was used for statistical analyses.…”
Section: Methodsmentioning
confidence: 87%
“…Therefore, appropriate evaluation and management of dysphagia are important in Japan which has already become an aging society. Toda et al [9] conducted swallowing rounds in patients admitted to an acute hospital, and reported significant improvements in food texture, eating status scale (ESS) score [10], and dysphagia severity scale (DSS) score [10]. However, there are very few reports of large-scale studies on the evaluation and management of dysphagia in acute hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…There are knowledge and skills that all caregivers should have and that are provided by the professions so that meals can be served safely with a multidisciplinary perspective. Studies have reported [9,10] that multidisciplinary care teams can provide ward rounds for suspected dysphagia patients in hospitals and this team care contributes to improving their swallowing ability. Such treatment can be applied to nursing home residents.…”
Section: Discussionmentioning
confidence: 99%